KEDUDUKAN AKTA HIBAH DALAM SENGKETA KEPEMILIKAN HAK ATAS TANAH - Putri Wardhani (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTGrant is a one-sided agreement whichis the parties who are still alive, freelyand irrevocable, give or dissectingan object for the purpose of therecipient's receiving the comforter. Aa common problem in society is thattransitions land of rights through thegrants. This is could happen whensomeone wrong. The wrong partiessaid that they felt like had the grantor the parties who inherited thegrant. The solution should beestablished by viewing the form ofthe grant performed using anauthentic deed as prescribed inarticle 1682 of civil law. The generalthe authority is given to make the seed ofthe grant by the law is the land deed.The issue raised in this writing wasentitled. "The study was intended toanswer the question of how the deedof the grant was valid and theposition of the grant deed in disputeover the land rights. The type ofresearch that used, wasnormative-juridical research, a studydone on the basis of legal materialsand by the way of collecting data,studying books on the librariesrelated to this research.As for the conclusion of this study,a grant is a free form of a covenantthat only submit to the terms of thetreaty set. That the terms of the covenantregulated in civil law. Thethe legitimacy of the rights that shouldbe extended to the recipient and thethe object should be given to be free ofcharge, interference, and litigationon the part of the third parties.Material obtained from anillegitimate grant, wouldautomatically render theunauthorized as an objectinheritance, so that the recipientwould be denied by the acquiresobject.Keywords: Deeds, Grants, RightsOn The Land.